Anti-UV isosorbide polycarbonate copolymer and preparation method thereof

By copolymerizing isosorbide, hydroxyl-containing triazine compounds and carbonate diesters, UV-resistant isosorbate polycarbonate copolymers are prepared, which solves the problem of polycarbonate easily discoloration and degradation under ultraviolet light, and significantly improves the problem of polycarbonate being easily discolored and degraded under ultraviolet light, thus further improving the The material has UV resistance, thermal stability and anti-aging properties, meets the performance requirements of related application fields, and is environmentally friendly in preparation and has a wide range of raw materials.

CN119241825APending Publication Date: 2025-01-03SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411691903.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Isosorbate polycarbonate is prone to discoloration and degradation under ultraviolet rays or outdoor sunlight, resulting in a significant decline in physical and chemical performance indicators such as insulation and strength, which cannot meet the requirements of related application fields.

Method used

Isorbitol, hydroxyl-containing triazine compounds and carbonate diesters as polymer monomers are used to prepare UV-resistant isosorbitol-type polycarbonate copolymers through transesterification and polycondensation reaction, and use appropriately during the preparation process. Catalysts and additives to improve the material's resistance to UV, thermal stability and anti-aging.

Benefits of technology

It significantly improves UV resistance, thermal stability and anti-aging performance, meets the performance requirements of related application fields, and has environmentally friendly preparation methods and a wide range of sources of reaction raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241825A_ABST
    Figure CN119241825A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-UV isosorbide polycarbonate copolymer and a preparation method thereof, and belongs to the technical field of high-molecular polycarbonate. The technical problem to be solved by the invention is to provide the anti-UV isosorbide polycarbonate copolymer. Polymeric monomers of the copolymer comprise isosorbide, a hydroxyl-containing triazine compound and diester carbonate, and the molar ratio of the isosorbide to the hydroxyl-containing triazine compound to the diester carbonate is (0.9-0.5): (0.1-0.5): 1. According to the invention, isosorbide and a hydroxyl-containing triazine compound are taken as polyhydric alcohols and are copolymerized with diester carbonate, so that the efficient anti-UV bio-based polycarbonate is obtained, and the properties such as UV resistance, thermal stability and aging resistance of the polycarbonate are obviously improved. According to the preparation method of the anti-UV isosorbide polycarbonate, the reaction raw materials are wide in source, the reaction process is green and environment-friendly, and the preparation method is worthy of being widely popularized and applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a UV-resistant isosorbide-type polycarbonate copolymer and a preparation method thereof, and belongs to the technical field of high molecular weight polycarbonate. Background Art

[0002] Isosorbide is a bio-based chemical raw material obtained from sorbitol through secondary intramolecular dehydration. It has the advantages of wide sources, green environmental protection and low price. It is widely used in food, medicine, fine chemicals, chemical intermediates and polymer materials. When it is used as a comonomer in the synthesis of polycarbonate, it can improve the optical transparency and impact resistance of the polymer.

[0003] Whether it is isosorbide-based polycarbonate or other types of polycarbonate, since UV radiation accelerates the chain breakage of polycarbonate, these polymers are prone to discoloration and degradation under long-term exposure to ultraviolet rays or outdoor sunlight, resulting in a significant decrease in physical and chemical performance indicators such as insulation and strength, which has a serious impact on the mechanical, electrical and optical properties of the material and cannot meet the requirements of related application fields.

[0004] The Chinese invention patent application with application number 202311555887.6 discloses a bio-based polycarbonate material specially used for high-end optical lenses and its preparation method. Isosorbide-type polycarbonate, polymethyl methacrylate, lanthanum oxide, nano-zinc oxide, nano-silica, cross-linking agent, ultraviolet absorber, light stabilizer and antioxidant are blended and extruded into granules to obtain a bio-based polycarbonate material with higher refractive index and transmittance.

[0005] The Chinese invention patent application with application number 202010373339.1 discloses a method of preparing a bio-based polycarbonate with certain anti-ultraviolet properties by blending isosorbide-type polycarbonate, polymethyl methacrylate, nano-silica, a cross-linking agent, ultraviolet absorber UV234, etc. in a certain proportion under stirring conditions.

[0006] However, the above method only uses a small amount of ultraviolet absorber as an additive, which can only slightly improve the anti-ultraviolet performance of the polymer and cannot meet the requirements of related application fields. Summary of the invention

[0007] In view of the above defects, the first technical problem solved by the present invention is to provide a UV-resistant (i.e., ultraviolet-resistant) isosorbide-based polycarbonate copolymer.

[0008] The UV-resistant isosorbide polycarbonate copolymer of the invention comprises isosorbide, a hydroxyl-containing triazine compound and a carbonic acid diester as polymerization monomers, and the molar ratio of the isosorbide, the hydroxyl-containing triazine compound and the carbonic acid diester is 0.5-0.9:0.1-0.5:1.

[0009] In a preferred embodiment of the present invention, the molar ratio of isosorbide, hydroxyl-containing triazine compound and carbonic acid diester is 0.7:0.3:1.

[0010] In one embodiment of the present invention, the carbonic acid diester is at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, dibutyl carbonate, dipentyl carbonate, dihexyl carbonate, dioctyl carbonate, diphenyl carbonate, ditolyl carbonate, and dinaphthyl carbonate. In some specific embodiments, the carbonic acid diester is at least one of dimethyl carbonate, diethyl carbonate, and diphenyl carbonate. In a specific embodiment, the carbonic acid diester is dimethyl carbonate.

[0011] In one embodiment of the present invention, the hydroxyl-containing triazine compound is (9ci)-1,2,3,6-tetrahydro-1,3-dihydroxy-2,4-dimethyl-1,3,5-triazine.

[0012] In one embodiment of the present invention, the number average molecular weight of the UV-resistant isosorbide polycarbonate copolymer is 2×10 4 ~5×10 4 In some embodiments, the number average molecular weight of the UV-resistant isosorbide polycarbonate copolymer is 3×10 4 ~4×10 4 .

[0013] The second technical problem solved by the present invention is to provide a method for preparing the UV-resistant isosorbide-based polycarbonate copolymer of the present invention.

[0014] The method for preparing the UV-resistant isosorbide-based polycarbonate copolymer of the present invention comprises the following steps:

[0015] 1) Transesterification reaction: isosorbide, hydroxyl-containing triazine compounds, carbonic acid diester and catalyst are mixed and transesterification reaction is carried out under protective atmosphere;

[0016] 2) Polycondensation reaction: When the esterification rate of the transesterification reaction is above 90%, the temperature is raised to carry out polycondensation reaction to obtain UV-resistant isosorbide-type polycarbonate copolymer.

[0017] In one embodiment of the present invention, the catalyst is at least one of metal hydroxides, metal oxides, metal hydrides, metal acetylacetonate complexes, alkoxy metal compounds, metal bicarbonates, metal alkanoates, metal phosphates, metal hydrogen phosphates, titanium organic compounds, tin organic compounds, inorganic acids, organic acids, organic amines and metal halides. In some specific embodiments, the catalyst is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium oxide, lithium hydride, calcium hydride, lithium acetylacetonate, sodium acetylacetonate, potassium acetylacetonate, magnesium acetylacetonate, zinc acetylacetonate, calcium acetylacetonate, tetraethoxytitanium, tetraisopropyl titanate, tetrabutyl titanate, dibutyltin oxide, stannous octoate, dibutyltin dilaurate, potassium methoxide, sodium methoxide, potassium carbonate, sodium carbonate, lithium carbonate, cesium carbonate, potassium bicarbonate, sodium bicarbonate, phosphoric acid, sodium phosphate, sodium hydrogen phosphate, acetic acid, p-toluenesulfonic acid, m-toluenesulfonic acid, benzenesulfonic acid, trimethylamine, triethylamine, dimethylaminopyridine, potassium acetate, lithium acetate, sodium acetate, zinc acetate, magnesium acetate, manganese acetate, sodium stearate, magnesium stearate, potassium stearate, calcium stearate, zinc stearate, sodium chloride, lithium chloride, potassium chloride, and cesium chloride. In a specific embodiment, the catalyst is lithium acetylacetonate.

[0018] In some specific embodiments, the amount of the catalyst is 0.05% to 0.5% of the amount of the carbonic acid diester, and preferably the amount of the catalyst is 0.1% of the amount of the carbonic acid diester.

[0019] In one embodiment of the present invention, in step 1), the pressure of the ester exchange reaction is 0.01-0.06 MPa, the reaction temperature is 180-210°C, and the reaction time is 3-4 hours; in step 2), the pressure of the polycondensation reaction is 80-140 Pa, the reaction temperature is 210-250°C, and the reaction time is 2-3 hours.

[0020] In one specific embodiment, in step 1), the reaction temperature of the transesterification reaction is 190°C and the reaction time is 3 hours; in step 2), the pressure of the polycondensation reaction is 100 Pa, the reaction temperature is 220°C, and the reaction time is 2 hours. In one specific embodiment, in step 1), the transesterification reaction is specifically: heating to 190°C and reacting at 0.06MPa for 1 hour, then adjusting to 0.04MPa for 1 hour, and finally adjusting to 0.01MPa for 1 hour.

[0021] The invention also provides a UV-resistant isosorbide-type polycarbonate material.

[0022] The UV-resistant isosorbide polycarbonate material of the present invention comprises a UV-resistant isosorbide polycarbonate copolymer and an auxiliary agent, wherein the weight percentage of the UV-resistant isosorbide polycarbonate copolymer is more than 90% based on the weight of the UV-resistant isosorbide polycarbonate material being 100%.

[0023] The commonly used auxiliary agents in the art are all applicable to the present invention. In some specific embodiments, the auxiliary agent is at least one of an antistatic agent, an anti-dripping agent, and an antioxidant.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The invention uses isosorbide and hydroxyl-containing triazine compounds as polyols to copolymerize with carbonic acid diesters to obtain high-efficiency UV-resistant bio-based polycarbonate, and the polycarbonate has significantly improved UV resistance, thermal stability, aging resistance and other properties. The preparation method of the UV-resistant isosorbide polycarbonate of the invention has a wide range of reaction raw materials, and the reaction process is green and environmentally friendly, and is worthy of large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The product T-PIC-1 prepared in Example 1 1 H-NMR spectrum. DETAILED DESCRIPTION

[0027] The UV-resistant isosorbide polycarbonate copolymer of the invention comprises isosorbide, a hydroxyl-containing triazine compound and a carbonic acid diester as polymerization monomers, and the molar ratio of the isosorbide, the hydroxyl-containing triazine compound and the carbonic acid diester is 0.5-0.9:0.1-0.5:1.

[0028] Hydroxyl-containing triazine compounds are often used as ultraviolet absorbers, and their molecular structure contains three nitrogen atoms and several carbon atoms, usually with a triazine ring as the main body and a hydroxyl group as a substituent. The present invention uses it as a comonomer to improve the chemical stability, heat resistance, aging resistance and UV resistance of isosorbide-based polycarbonate.

[0029] In a preferred embodiment of the present invention, the molar ratio of isosorbide, hydroxyl-containing triazine compound and carbonic acid diester is 0.7:0.3:1.

[0030] Carbonic acid diesters commonly used in the art are only applicable to the present invention, including but not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, dibutyl carbonate, dipentyl carbonate, dihexyl carbonate, dioctyl carbonate, diphenyl carbonate, ditolyl carbonate, and dinaphthyl carbonate. In some specific embodiments, the carbonic acid diester is at least one of dimethyl carbonate, diethyl carbonate, and diphenyl carbonate. In a specific embodiment, the carbonic acid diester is dimethyl carbonate.

[0031] In one embodiment of the present invention, the hydroxyl-containing triazine compound is (9ci)-1,2,3,6-tetrahydro-1,3-dihydroxy-2,4-dimethyl-1,3,5-triazine. Specifically, the structural formula of the (9ci)-1,2,3,6-tetrahydro-1,3-dihydroxy-2,4-dimethyl-1,3,5-triazine is:

[0032]

[0033] In one embodiment of the present invention, the number average molecular weight of the UV-resistant isosorbide polycarbonate copolymer is 2×10 4 ~5×10 4 In some embodiments, the number average molecular weight of the UV-resistant isosorbide polycarbonate copolymer is 3×10 4 ~4×10 4 .

[0034] The second technical problem solved by the present invention is to provide a method for preparing the UV-resistant isosorbide-based polycarbonate copolymer of the present invention.

[0035] The method for preparing the UV-resistant isosorbide-based polycarbonate copolymer of the present invention comprises the following steps:

[0036] 1) Transesterification reaction: isosorbide, hydroxyl-containing triazine compounds, carbonic acid diester and catalyst are mixed and transesterification reaction is carried out under protective atmosphere;

[0037] 2) Polycondensation reaction: When the esterification rate of the transesterification reaction is above 90%, the temperature is raised to carry out polycondensation reaction to obtain UV-resistant isosorbide-type polycarbonate copolymer.

[0038] Taking dimethyl carbonate as an example, the reaction process of the preparation method of the UV-resistant isosorbide-based polycarbonate copolymer of the present invention is as follows:

[0039]

[0040] The catalyst may be a conventional catalyst in the art, including but not limited to at least one of metal hydroxides, metal oxides, metal hydrides, metal acetylacetonate complexes, alkoxy metal compounds, metal bicarbonates, metal alkanoates, metal phosphates, metal hydrogen phosphates, titanium organic compounds, tin organic compounds, inorganic acids, organic acids, organic amines and metal halides. In some specific embodiments, the catalyst is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium oxide, lithium hydride, calcium hydride, lithium acetylacetonate, sodium acetylacetonate, potassium acetylacetonate, magnesium acetylacetonate, zinc acetylacetonate, calcium acetylacetonate, tetraethoxytitanium, tetraisopropyl titanate, tetrabutyl titanate, dibutyltin oxide, stannous octoate, dibutyltin dilaurate, potassium methoxide, sodium methoxide, potassium carbonate, sodium carbonate, lithium carbonate, cesium carbonate, potassium bicarbonate, sodium bicarbonate, phosphoric acid, sodium phosphate, sodium hydrogen phosphate, acetic acid, p-toluenesulfonic acid, m-toluenesulfonic acid, benzenesulfonic acid, trimethylamine, triethylamine, dimethylaminopyridine, potassium acetate, lithium acetate, sodium acetate, zinc acetate, magnesium acetate, manganese acetate, sodium stearate, magnesium stearate, potassium stearate, calcium stearate, zinc stearate, sodium chloride, lithium chloride, potassium chloride, and cesium chloride. In a specific embodiment, the catalyst is lithium acetylacetonate.

[0041] The amount of the catalyst is conventional in the art. In some embodiments, the amount of the catalyst is 0.05% to 0.5% of the amount of the carbonate diester, preferably 0.1% of the amount of the carbonate diester.

[0042] Step 1) is an ester exchange reaction, in which isosorbide, hydroxyl-containing triazine compounds and carbonic acid diester react under a protective atmosphere. In one embodiment of the present invention, the pressure of the ester exchange reaction is 0.01-0.06MPa, the reaction temperature is 180-210°C, and the reaction time is 3-4h. In a specific embodiment, the reaction temperature of the ester exchange reaction is 190°C and the reaction time is 3h. In a specific embodiment, the ester exchange reaction is specifically: heating to 190°C and reacting at 0.06MPa for 1h, then adjusting to 0.04MPa for 1h, and finally adjusting to 0.01MPa for 1h.

[0043] The protective atmosphere described in the present invention is an atmosphere that does not participate in the reaction, including but not limited to an inert atmosphere such as helium, neon, argon, or a nitrogen atmosphere.

[0044] The ester exchange reaction will also produce by-products. The by-products generated during the reaction and the distilled raw materials are passed through a spherical condenser filled with hot water and finally collected in a round-bottom flask for collection and separation. The polycondensation reaction is carried out for a period of time, and the esterification rate is calculated based on the collected by-products.

[0045] Step 2) is a polycondensation reaction. When the esterification rate of the transesterification reaction is above 90%, the reaction solution gradually becomes clear, and the temperature is raised to carry out the polycondensation reaction. When no by-products are produced, the reaction is terminated to obtain a UV-resistant isosorbide-type polycarbonate copolymer. In one embodiment of the present invention, the pressure of the polycondensation reaction is 80-140 Pa, the reaction temperature is 210-250° C., and the reaction time is 2-3 h. In a specific embodiment, the pressure of the polycondensation reaction is 100 Pa, the reaction temperature is 220° C., and the reaction time is 2 h.

[0046] The invention also provides a UV-resistant isosorbide-type polycarbonate material.

[0047] The UV-resistant isosorbide polycarbonate material of the present invention comprises a UV-resistant isosorbide polycarbonate copolymer and an auxiliary agent, wherein the weight percentage of the UV-resistant isosorbide polycarbonate copolymer is more than 90% based on the weight of the UV-resistant isosorbide polycarbonate material being 100%.

[0048] The commonly used auxiliary agents in the art are all applicable to the present invention. In some specific embodiments, the auxiliary agent is at least one of an antistatic agent, an anti-dripping agent, and an antioxidant.

[0049] In some specific embodiments, the antistatic agent is sodium alkylbenzene sulfonate, the anti-dripping agent is polytetrafluoroethylene powder, and the antioxidant is at least one of RIANOX1076 and RIANOX168. Among them, RIANOX168 is antioxidant 168, that is, tris[2,4-di-tert-butylphenyl]phosphite, and RIANOX1076 is antioxidant 1076, that is, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0050] The specific implementation of the present invention is further described below in conjunction with the examples, but the present invention is not limited to the scope of the examples. The hydroxyl-containing triazine compounds in the examples are all commercially available (9ci)-1,2,3,6-tetrahydro-1,3-dihydroxy-2,4-dimethyl-1,3,5-triazine.

[0051] Example 1

[0052] 1) 2,5-dihydroxyisosorbide (IS), dimethyl carbonate (DMC), hydroxyl-containing triazine compounds and lithium acetylacetonate were placed in a flask at a molar ratio of 0.9:1:0.1:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1h, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1h, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1h. The methanol generated during the reaction passed through a spherical condenser filled with hot water and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0053] 2) When the transesterification rate reached 90%, the temperature was raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol was produced, the reaction was terminated to obtain the product T-PIC-1, whose number average molecular weight was 3.915×10 4 Its H NMR spectrum 1 H-NMR Figure 1 .

[0054] 3) The homemade T-PIC-1 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 1.

[0055] Table 1 Extrusion raw material composition of Example 1

[0056] raw material Content (wt.%) Homemade T-PIC-1 94.3 Antistatic agent (sodium alkylbenzene sulfonate) 5 Anti-drip agent (PTFE powder) 0.3 Antioxidant 1 (RIANOX1076) 0.2 Antioxidant 2 (RIANOX168) 0.2

[0057] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them well, then add the well mixed mixture into a twin screw extruder for melt extrusion, the extruder temperature is: zone 1 210°C, zone 2 230°C, zone 3 230°C, zone 4: 230°C, zone 5 220°C, zone 6 220°C, die head 230°C. After cooling in a water tank, pelletizing and packaging are obtained to obtain UV resistant isosorbide polycarbonate pellets T-PIC-1.

[0058] Example 2

[0059] 1) 2,5-dihydroxyisosorbide (IS), dimethyl carbonate (DMC), hydroxyl-containing triazine compounds and lithium acetylacetonate were added into a flask at a molar ratio of 0.8:1:0.2:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1h, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1h, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1h. The methanol generated during the reaction passed through a spherical condenser filled with hot water and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0060] 2) When the transesterification rate reaches 90%, the temperature is raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol is produced, the reaction ends and the product T-PIC-2 is obtained, with a number average molecular weight of 3.897×10 4 .

[0061] 3) The homemade T-PIC-2 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 2.

[0062] Table 2 Extrusion raw material composition of Example 2

[0063]

[0064]

[0065] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them well, then add the well mixed mixture into a twin screw extruder for melt extrusion, the extruder temperature is: zone 1 210°C, zone 2 230°C, zone 3 230°C, zone 4: 230°C, zone 5 220°C, zone 6 220°C, die head 230°C. After cooling in a water tank, pelletizing and packaging are obtained to obtain UV resistant isosorbide polycarbonate pellets T-PIC-2.

[0066] Example 3

[0067] 1) 2,5-dihydroxyisosorbide (IS), dimethyl carbonate (DMC), hydroxyl-containing triazine compounds and lithium acetylacetonate were added into a flask at a molar ratio of 0.7:1:0.3:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1h, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1h, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1h. The methanol generated during the reaction passed through a spherical condenser filled with hot water and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0068] 2) When the transesterification rate reached 90%, the temperature was raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol was produced, the reaction was terminated to obtain the product T-PIC-3, whose number average molecular weight was 3.798×10 4 .

[0069] 3) The homemade T-PIC-3 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 3.

[0070] Table 3 Extrusion raw material composition of Example 3

[0071] raw material Content (wt.%) Homemade T-PIC-3 94.3 Antistatic agent (sodium alkylbenzene sulfonate) 5 Anti-drip agent (PTFE powder) 0.3 Antioxidant 1 (RIANOX1076) 0.2 Antioxidant 2 (RIANOX168) 0.2

[0072] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them evenly, then add the evenly mixed mixture into a twin-screw extruder for melt extrusion. The extruder temperature is: 210°C in zone 1, 230°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, and 230°C in die head. After cooling in a water tank, pelletizing and packaging are performed to obtain UV-resistant isosorbide polycarbonate pellets T-PIC-3.

[0073] Example 4

[0074] 1) 2,5-dihydroxyisosorbide (IS), dimethyl carbonate (DMC), hydroxyl-containing triazine compounds and lithium acetylacetonate were added into a flask at a molar ratio of 0.6:1:0.4:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1h, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1h, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1h. The methanol generated during the reaction passed through a spherical condenser filled with hot water and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0075] 2) When the transesterification rate reaches 90%, the temperature is raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol is produced, the reaction ends and the product T-PIC-4 is obtained, with a number average molecular weight of 3.725×10 4 .

[0076] 3) The homemade T-PIC-4 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 4.

[0077] Table 4 Extrusion raw material composition of Example 4

[0078] raw material Content (wt.%) Homemade T-PIC-4 94.3 Antistatic agent (sodium alkylbenzene sulfonate) 5 Anti-drip agent (PTFE powder) 0.3 Antioxidant 1 (RIANOX1076) 0.2 Antioxidant 2 (RIANOX168) 0.2

[0079] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them evenly, then add the evenly mixed mixture into a twin-screw extruder for melt extrusion. The extruder temperature is: zone 1 210°C, zone 2 230°C, zone 3 230°C, zone 4: 230°C, zone 5 220°C, zone 6 220°C, and die head 230°C. After cooling in a water tank, pelletizing and packaging are obtained to obtain UV-resistant isosorbide polycarbonate pellets T-PIC-4.

[0080] Example 5

[0081] 1) 2,5-dihydroxyisosorbide (IS), dimethyl carbonate (DMC), hydroxyl-containing triazine compounds and lithium acetylacetonate were added into a flask at a molar ratio of 0.5:1:0.5:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1h, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1h, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1h. The methanol generated during the reaction passed through a spherical condenser filled with hot water and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0082] 2) When the transesterification rate reaches 90%, the temperature is raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol is produced, the reaction ends and the product T-PIC-5 is obtained, with a number average molecular weight of 3.698×10 4 .

[0083] 3) The homemade T-PIC-5 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 5.

[0084] Table 5 Extrusion raw material composition of Example 5

[0085]

[0086]

[0087] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them thoroughly and evenly, then add the thoroughly mixed mixture into a twin-screw extruder for melt extrusion. The extruder temperature is: 210°C in zone 1, 230°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, and 230°C in die head.

[0088] After cooling in a water tank, the pellets are cut and packaged to obtain UV-resistant isosorbide polycarbonate pellets T-PIC-5.

[0089] Comparative Example 1

[0090] 1) 2,5-dihydroxyisosorbide (IS), dimethyl carbonate (DMC) and lithium acetylacetonate were added into a flask at a molar ratio of 1.0:1.0:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1h, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1h, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1h. The methanol generated during the reaction passed through a spherical condenser filled with hot water, and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0091] 2) When the transesterification rate reaches 90%, the temperature is raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol is produced, the reaction ends and the product PIC-0 is obtained, with a number average molecular weight of 3.924×10 4 .

[0092] 3) The homemade PIC-0 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 6.

[0093] Table 6 Extrusion raw material composition of comparative example 1

[0094] raw material Content (wt.%) Homemade PIC-0 94.3 Antistatic agent (sodium alkylbenzene sulfonate) 5 Anti-drip agent (PTFE powder) 0.3 Antioxidant 1 (RIANOX1076) 0.2 Antioxidant 2 (RIANOX168) 0.2

[0095] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them evenly, then add the evenly mixed mixture into a twin-screw extruder for melt extrusion. The extruder temperature is: 210°C in zone 1, 230°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, and 230°C in die head. After cooling in a water tank, the mixture is pelletized and packaged to obtain isosorbide polycarbonate pellets PIC-0.

[0096] Comparative Example 2

[0097] 1) Hydroxyl-containing triazine compounds, dimethyl carbonate (DMC) and lithium acetylacetonate were placed in a flask at a molar ratio of 1.0:1.0:0.001, and the ester exchange reaction was carried out at 190°C and a pressure of 0.06MPa for 1 hour, and then the pressure was adjusted to 0.04MPa, and the reaction was continued for another 1 hour, and finally the pressure was adjusted to 0.01MPa, and the reaction was continued for 1 hour. The methanol generated during the reaction passed through a spherical condenser filled with hot water, and was finally collected in a round-bottom flask for collection and separation, and the ester exchange rate was calculated based on the collected by-product methanol.

[0098] 2) When the transesterification rate reaches 90%, the temperature is raised to 220°C and polycondensed at 100 Pa for about 2 hours. When no methanol is produced, the reaction ends and the product PTC-0 is obtained, with a number average molecular weight of 3.259×10 4 .

[0099] 3) The homemade PTC-0 was crushed with a crusher, dried at 100°C for 12 h, blended with other additives, and melt-extruded. The raw material composition is shown in Table 7.

[0100] Table 7 Extrusion raw material composition of comparative example 2

[0101] raw material Content (wt.%) Homemade PTC-0 94.3 Antistatic agent (sodium alkylbenzene sulfonate) 5 Anti-drip agent (PTFE powder) 0.3 Antioxidant 1 (RIANOX1076) 0.2 Antioxidant 2 (RIANOX168) 0.2

[0102] 4) Put the above raw materials into a stirring pot and stir for 5 minutes to mix them well, then add the well mixed mixture into a twin screw extruder for melt extrusion, the extruder temperature is: zone 1 210°C, zone 2 230°C, zone 3 230°C, zone 4: 230°C, zone 5 220°C, zone 6 220°C, die head 230°C. After cooling in a water tank, pelletizing and packaging are obtained to obtain polycarbonate pellets PTC-0 containing a triazine structure.

[0103] The properties of the polycarbonate pellets obtained in the examples and comparative examples were measured, and the results are shown in Table 8. The melt flow rate test standard is ISO 1133; the tensile strength test standard is ISO 527; the flexural strength test standard is ISO 178; the notched impact strength reduction test standard is ISO 179-1 / 1eU; the light aging performance test standard is: equipment: SAE J241, irradiance: (0.55±0.01)W / (m2 ·nm)@340nm, light: 3.8h, blackboard temperature: (89±2.5)℃, relative humidity: (50±10)℃, dark: 1h, blackboard temperature: (38±2.5)℃, relative humidity: (95±10)℃, filter: Quartz / Boro, irradiation: 488kJ / m 2 ; The elongation at break test standard is ISO 527; The UV transmittance test is the average transmittance in the UV region of 280-380nm.

[0104] Table 8 Test results of Examples 1 to 5 and Comparative Examples 1 to 2

[0105]

[0106]

[0107] In summary, the present invention obtains UV-resistant polycarbonate with good performance by copolymerizing isosorbide and hydroxyl-containing triazine compounds as polyols with carbonic acid diesters.

Claims

1. UV-resistant isosorbide-based polycarbonate copolymer, characterized in that: The polymerization monomers of the copolymer include isosorbide, a triazine compound containing a hydroxyl group and a carbonic acid diester, and the molar ratio of the isosorbide, the triazine compound containing a hydroxyl group and the carbonic acid diester is 0.5-0.9:0.1-0.5:

1.

2. The UV-resistant isosorbide-based polycarbonate copolymer according to claim 1, characterized in that: The molar ratio of isosorbide, the hydroxyl-containing triazine compound and the carbonic acid diester is 0.7:0.3:

1.

3. The UV-resistant isosorbide-based polycarbonate copolymer according to claim 1, characterized in that: The carbonate diester is at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, dibutyl carbonate, dipentyl carbonate, dihexyl carbonate, dioctyl carbonate, diphenyl carbonate, ditolyl carbonate and dinaphthyl carbonate; the hydroxyl-containing triazine compound is (9ci)-1,2,3,6-tetrahydro-1,3-dihydroxy-2,4-dimethyl-1,3,5-triazine; preferably, the carbonate diester is at least one of dimethyl carbonate, diethyl carbonate and diphenyl carbonate; more preferably, the carbonate diester is dimethyl carbonate.

4. The UV-resistant isosorbide-based polycarbonate copolymer according to claim 1, characterized in that: The number average molecular weight of the copolymer is 2×10 4 ~5×10 4 The number average molecular weight of the copolymer is preferably 3×10 4 ~4×10 4 .

5. The method for preparing the UV-resistant isosorbide-based polycarbonate copolymer according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Transesterification reaction: isosorbide, hydroxyl-containing triazine compounds, carbonic acid diester and catalyst are mixed and transesterification reaction is carried out under protective atmosphere; 2) Polycondensation reaction: When the esterification rate of the transesterification reaction is above 90%, the temperature is raised to carry out polycondensation reaction to obtain UV-resistant isosorbide-type polycarbonate copolymer.

6. The method for preparing the UV-resistant isosorbide-based polycarbonate copolymer according to claim 5, characterized in that: The catalyst is at least one of metal hydroxides, metal oxides, metal hydrides, metal acetylacetonate complexes, alkoxy metal compounds, metal bicarbonates, metal alkanoates, metal phosphates, metal hydrogen phosphates, titanium organic compounds, tin organic compounds, inorganic acids, organic acids, organic amines and metal halides; preferably, the catalyst is lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium oxide, lithium hydride, calcium hydride, lithium acetylacetonate, sodium acetylacetonate, potassium acetylacetonate, magnesium acetylacetonate, zinc acetylacetonate, calcium acetylacetonate, tetraethoxytitanium, tetraisopropyl titanate, titanium The catalyst is preferably selected from the group consisting of tetrabutyl tin, dibutyltin oxide, stannous octoate, dibutyltin dilaurate, potassium methoxide, sodium methoxide, potassium carbonate, sodium carbonate, lithium carbonate, cesium carbonate, potassium bicarbonate, sodium bicarbonate, phosphoric acid, sodium phosphate, sodium hydrogen phosphate, acetic acid, p-toluenesulfonic acid, m-toluenesulfonic acid, benzenesulfonic acid, trimethylamine, triethylamine, dimethylaminopyridine, potassium acetate, lithium acetate, sodium acetate, zinc acetate, magnesium acetate, manganese acetate, sodium stearate, magnesium stearate, potassium stearate, calcium stearate, zinc stearate, sodium chloride, lithium chloride, potassium chloride, and cesium chloride, and more preferably the catalyst is lithium acetylacetonate.

7. The method for preparing the UV-resistant isosorbide-based polycarbonate copolymer according to claim 5, characterized in that: The amount of the catalyst used is 0.05% to 0.5% of the amount of the carbonic acid diester, and preferably 0.1% of the amount of the carbonic acid diester.

8. The method for preparing the UV-resistant isosorbide-based polycarbonate copolymer according to claim 4, characterized in that: In step 1), the pressure of the transesterification reaction is 0.01-0.06MPa, the reaction temperature is 180-210°C, and the reaction time is 3-4h; in step 2), the pressure of the polycondensation reaction is 80-140Pa, the reaction temperature is 210-250°C, and the reaction time is 2-3h; preferably, in step 1), the reaction temperature of the transesterification reaction is 190°C, and the reaction time is 3h; in step 2), the pressure of the polycondensation reaction is 100Pa, the reaction temperature is 220°C, and the reaction time is 2h; more preferably, in step 1), the transesterification reaction is specifically: heating to 190°C and reacting at 0.06MPa for 1h, then adjusting to 0.04MPa for 1h, and finally adjusting to 0.01MPa for 1h.

9. UV-resistant isosorbide-based polycarbonate material, characterized in that: The invention comprises the UV-resistant isosorbide polycarbonate copolymer according to any one of claims 1 to 4 and an auxiliary agent, wherein the weight percentage of the UV-resistant isosorbide polycarbonate copolymer is more than 90%.

10. The UV-resistant isosorbide-based polycarbonate material according to claim 9, characterized in that: The auxiliary agent is at least one of an antistatic agent, an anti-dripping agent, and an antioxidant.

Citation Information

Cited By

  • Anti-aging polyvinyl chloride sheet and preparation method thereof

    CN119735902A